THE BACTERIOLOGY OF OIL SARDINE (SARDINELLA LONGICEPS) AND MACKEREL (RASTRELLIGER KANAGURTA) FROM TROPICAL WATERS OFF COCHIN -II QUANTITATIVE ASPECTS - SURENDRAN, P K; GOPAKUMAR, K (Fishery Technology, 2017)
80% of the flora of skin, gills and intestines of oil sardine and mackerel at. isolation temperature 28 ±2°C consisted of Gram negative asporogenous rods or cocci, belon.ging to the genera Vibrio, Pseudomonas, Moraxella, Acinetobacter and Flavobacterzaj Cytophaga. Nearly 10% of the flora was constituted by Gram positives, Micrococcus and Arthrobacter. Incubation temperature of 36 ± 1 oc recovered more Vibrio spp. and Gram positives, while at lower temperatures of 8 ± 1 oc and 1 ± 1 °C, more Pseu1omonas, Acinetobacter and M oraxella spp. were recovered. Significant changes wrth respect to season were observed in the relative distribution of different genera.